The point slope form:
[tex]y - y_1 = m(x - x_1)[/tex]
We need to find the slope. To find the slope we can use the following formula:
[tex]\frac{y_2 - y_1}{x_2 - X_1}[/tex]
Use the points (-5, 6) and (0, 1) and plug it into our slope formula and solve:
[tex]\frac{1 - 6}{0 - (-5)}[/tex]
[tex]\frac{-5}{5} = -1[/tex]
So our slope is -1 which means m = slope = -1
Now that we have our slope lets create the point slope form
Our point slope form equation is [tex]y - y_1 = m(x - x_1)[/tex] Remember
m = slope = -1. Also, we are going to use the point (-5,6).
First insert the m = slope = -1 number where m is located
[tex]y - y_1 = -1(x - x_1)[/tex]
Next, insert the -5 from (-5,6) where [tex]x_1[/tex] is located and the 6 from (-5,6) where [tex]y_1[/tex] is located.
[tex]y - y_1 = -1(x - x_1)[/tex]
[tex]y - 6 = -1(x - (-5))[/tex]
Now simplify
[tex]y - 6 = -1(x - (-5))[/tex]
[tex]y - 6 = -1(x +5)[/tex] <-------Answer